2012
DOI: 10.1186/1746-1596-7-82
|View full text |Cite
|
Sign up to set email alerts
|

High MCM3 expression is an independent biomarker of poor prognosis and correlates with reduced RBM3 expression in a prospective cohort of malignant melanoma

Abstract: BackgroundMalignant melanoma is the most lethal form of skin cancer with a variable clinical course even in patients with thin melanomas and localized disease. Despite increasing insights into melanoma biology, no prognostic biomarkers have yet been incorporated into clinical protocols. Reduced expression of the RNA binding motif protein 3 (RBM3) has been shown to correlate with tumour progression and poor prognosis in melanoma and several other cancer forms. In ovarian cancer, an inverse association was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 32 publications
3
26
0
1
Order By: Relevance
“…For example, while RBM3 is thought to be a proto-oncogene that is upregulated in many cancers where it appears to protect cancer cells from mitotic catastrophe (19) or apoptosis (33), several studies also show that high RBM3 expression in cancer cells, especially in the nucleus, predicts a better prognosis in a variety of cancers, including prostate cancer (34)(35)(36)(37)(38)(39)(40). This negative correlation between RBM3 expression and tumor progression does not seem to support its oncogenic function but is in agreement with the present results showing decreased RBM3 expression in metastatic prostate cancer compared with primary cancer and, more importantly, that overexpression of RBM3 in PC3 cells greatly attenuates the stem cell-like feature of this aggressive cell line.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while RBM3 is thought to be a proto-oncogene that is upregulated in many cancers where it appears to protect cancer cells from mitotic catastrophe (19) or apoptosis (33), several studies also show that high RBM3 expression in cancer cells, especially in the nucleus, predicts a better prognosis in a variety of cancers, including prostate cancer (34)(35)(36)(37)(38)(39)(40). This negative correlation between RBM3 expression and tumor progression does not seem to support its oncogenic function but is in agreement with the present results showing decreased RBM3 expression in metastatic prostate cancer compared with primary cancer and, more importantly, that overexpression of RBM3 in PC3 cells greatly attenuates the stem cell-like feature of this aggressive cell line.…”
Section: Discussionmentioning
confidence: 99%
“…RBM3 overexpression is related to decreased cell death and increased cell proliferation . Immunohistochemical studies have shown that high nuclear RBM3 expression is associated with improved prognosis in an array of human malignancies, including melanoma, and breast, ovarian, oesophageal, gastric and urothelial bladder cancer . In prostate cancer, different prognostic impacts of RBM3 immunostaining results have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…7 Immunohistochemical studies have shown that high nuclear RBM3 expression is associated with improved prognosis in an array of human malignancies, including melanoma, and breast, ovarian, oesophageal, gastric and urothelial bladder cancer. [8][9][10][11][12][13][14][15] In prostate cancer, different prognostic impacts of RBM3 immunostaining results have been reported. Whereas one study suggested high RBM3 expression to be a good prognostic sign, 16 another recent large study on operated prostate cancer showed that high RBM3 expression is an independent prognostic marker of early biochemical recurrence, and is tightly linked to ERG activation and PTEN deletions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our research group has shown that MCM3 represents a useful proliferation biomarker to evaluate the progression of dysplastic lesions 8 . Previous studies have reported that some MCM family proteins may be associated with overall survival in various cancers such as gliomas, malignant melanoma, anaplastic astrocytoma and medulloblastoma 29,32,33,34 . Conversely, Ahn et al 35 did not find any relationship between the expression of MCM family proteins and overall survival in cases of squamous cell carcinoma of the esophagus.…”
Section: B) Immunoexpression Of Mcm3 In Oscc Epithelium (C) Moderatmentioning
confidence: 99%